Potatoes in the 1990s: Situation and prospects of the world potato economy - FAO (FAO, 1995)
This paper describes and analyzes the current structure of the world potato economy with emphasis on production, utilization and trade. The paper also looks into the future, outlines some of the constraints to further development of the potato sector and suggests areas for future action to overcome problems.